Living with kin in lowland horticultural societies - Walker, Robert S. (2013)
Postmarital residence patterns in traditional human societies figure prominently in models of hominid social evolution with arguments for patrilocal human bands similar in structure to female-dispersal systems in other African apes. However, considerable flexibility in hunter-gatherer cultures has led to their characterization as primarily multilocal. Horticulturalists are associated with larger, more sedentary social groups with more political inequality and intergroup conflict and may therefore provide additional insights into evolved human social structures. We analyze coresidence patterns of primary kin for 34 New World horticultural societies (6,833 adults living in 243 residential groupings) to show more uxorilocality (women live with more kin) than found for hunter-gatherers. Our findings further point to the uniqueness of human social structures and to considerable variation that is not fully described by traditional postmarital residence typologies. Sex biases in coresident kin can vary according to the scale of analysis (household vs. house cluster vs. village) and change across the life span, with women often living with more kin later in life. Headmen in large villages live with more close kin, primarily siblings, than do nonheadmen. Importantly, human marriage exchange and residence patterns create meta-group social structures, with alliances extending across multiple villages often united in competition against other large alliances at scales unparalleled by other species.